Glucocorticoids selectively inhibit the transcription of the interleukin 1 beta gene and decrease the stability of interleukin 1 beta mRNA. - Lee, S W (1988)
Transcription of the interleukin 1 beta (IL-1 beta) gene was studied by mRNA hybridization with a cDNA probe in the human promonocytic cell line U-937. Phorbol ester and lipopolysaccharide increased the steady-state level of IL-1 beta mRNA. Glucocorticoids markedly decreased IL-1 beta mRNA levels by two mechanisms. Transcription of the IL-1 gene was inhibited, as shown by in vitro transcription assays with nuclei isolated from glucocorticoid-treated cells. Moreover, kinetic analyses and pulse-labeling of mRNAs showed that glucocorticoids selectively decrease the stability of IL-1 beta mRNA, without affecting the stability of beta-actin and FOS mRNAs. Inhibition of the formation and effects IL-1 is a mechanism by which glucocorticoids can exert antiinflammatory and immunosuppressive effects.